2006
DOI: 10.1136/jmg.2005.034140
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of myopathy, encephalopathy, lactic acidosis, and stroke-like syndrome: contribution to understanding mitochondrial DNA segregation during human embryofetal development

Abstract: Introduction: Myopathy, encephalopathy, lactic acidosis, and stroke-like (MELAS) syndrome, a maternally inherited disorder that is among the most common mitochondrial DNA (mtDNA) diseases, is usually associated with the m.3242A.G mutation of the mitochondrial tRNA leu gene. Very few data are available with respect to prenatal diagnosis of this serious disease. The rate of mutant versus wild-type mtDNA (heteroplasmy) in fetal DNA is indeed considered to be a poor indicator of postnatal outcome. Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 13 publications
1
27
0
2
Order By: Relevance
“…Wang ZP, Department of Radiology, Beijing Tian Tan Hospital, Capital Medical University, Beijing 100050, China, e-mail: ping1023@139.com fatal [1,5]. In this paper, we report on a Chinese family afflicted by MELAS combined with diabetes and recurrent pancreatitis.…”
Section: Communicating Authormentioning
confidence: 98%
See 1 more Smart Citation
“…Wang ZP, Department of Radiology, Beijing Tian Tan Hospital, Capital Medical University, Beijing 100050, China, e-mail: ping1023@139.com fatal [1,5]. In this paper, we report on a Chinese family afflicted by MELAS combined with diabetes and recurrent pancreatitis.…”
Section: Communicating Authormentioning
confidence: 98%
“…MELAS, which forms a major clinical subgroup of the mitochondrial encephalomyopathies, is caused by any of several different single base replacements in the mt tRNA Leu(UUR) gene, which is responsible for the translation of UUR (R = A or G) leucine codons in mitochondrial genes [1][2][3][4][5]. It has been reported that 15% of patients with mitochondriopathies have symptoms of digestive disorders [3,7,14].…”
Section: Communicating Authormentioning
confidence: 99%
“…Although it is not possible to estimate heteroplasmy levels in individual tissues, and therefore not possible to predict clinical outcomes, prenatal genetic diagnosis has reportedly been applied successfully in several cases (Bouchet et al, 2006). Due to these uncertainties, parents are aiming to have offspring without any mutated mtDNA copies by the help of preimplantation genetic diagnosis (PGD) (Hellebrekers et al, 2012).…”
Section: Genetic Counselingmentioning
confidence: 99%
“…< Les femmes porteuses d'une mutation de l'ADNmt ont un risque élevé de transmettre une maladie grave à leur descendance, et beaucoup font la demande d'une prise en charge en diagnostic prénatal (DPN) et/ ou préimplantatoire (DPI). Ces procédures diagnostiques consistent à mesurer le taux d'hétéroplasmie foetal ou embryonnaire, et à considé-rer que les embryons et les foetus porteurs d'un taux d'hétéroplasmie inférieur au taux seuil de la mutation ont un risque faible de dévelop-per une cytopathie mitochondriale [1][2][3][4]. Cependant, la majorité des enfants nés après ce type de diagnostic sont porteurs de la mutation de l'ADNmt ce qui les expose à un risque résiduel de développer la maladie.…”
unclassified